Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1007/s004210000292
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical performance and electromyography during repeated maximal isokinetic shoulder forward flexions in female cleaners with and without myalgia of the trapezius muscle and in healthy controls

Abstract: This cross-sectional study aimed at investigating the influence of occupational exposure to static and highly repetitive work involving the neck and shoulder muscles, myalgia of and tender point in the trapezius muscle on biomechanical output, and electromyogram (EMG) variables (mean frequency MNF, signal amplitude and ability to relax) during maximal forward flexions of the shoulder muscles. Groups of 25 cleaners suffering from chronic myalgia of the trapezius muscle, 25 cleaners free from myalgia of the trap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 24 publications
2
36
0
2
Order By: Relevance
“…75 In subjects with neck pain, self-reported pain and disability ratings showed no correlation with strength measurements. 29,75,82 One study evaluated neck muscle endurance in patients with WAD compared with age-matched healthy controls. 83 Cervical flexor endurance tested in a supine position could distinguish well between WAD patients and the controls.…”
Section: Muscle Strength and Endurancementioning
confidence: 99%
See 1 more Smart Citation
“…75 In subjects with neck pain, self-reported pain and disability ratings showed no correlation with strength measurements. 29,75,82 One study evaluated neck muscle endurance in patients with WAD compared with age-matched healthy controls. 83 Cervical flexor endurance tested in a supine position could distinguish well between WAD patients and the controls.…”
Section: Muscle Strength and Endurancementioning
confidence: 99%
“…Muscle endurance measurement by electromyography for repeated forward flexion of the arm tested in people with neck pain and myalgia compared with symptom-free subjects was significantly lower. 82 …”
Section: Muscle Strength and Endurancementioning
confidence: 99%
“…Another hypothesis is related to an impaired ability to relax muscles in patients with RSI. 5,14,33 Veiersted et al 33 found that healthy women with lower rates of brief unconscious interruptions in muscle activity, monitored with electromyography, were prone to develop RSI symptoms over time. The finding suggests that continuous muscle activation during muscle tasks is a predisposing factor for the development of RSI symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…These shoulder-neck symptoms are generally classified into symptomatic and essential groups, with and without etiological factors such as orthopedics and medical disorders. Essential shoulder-neck pain is considered to develop and be exacerbated by corresponding muscle fatigue and hindered microcirculation due to repetitive tension of the shoulder-neck muscles 1,2) . Increases in both mental and physical stresses because of the recent increase in the popularity of information technology devices and the modification of the workplace environment are thought to be predominantly responsible for the increase in shoulder-neck problems.…”
Section: Introductionmentioning
confidence: 99%